SHGs and its Marketing Problems (Global Journal of Human-Social Science, 2013)
This paper is focused on the Problems of Self Help Groups. Women constitute nearly half of the rural population in India and play a vital role in Rural Economy. It is necessary for programmes specially targeted for a woman has been emphasized. As a result of the poverty alleviation scheme, such Integrated Rural Development Programme (IRDP), Training of Rural Youth for Self-employment (TRYSEM) and Development of Women and Children in Rural Areas (DWCRA) have been initiated. Self Help Groups are voluntary associations for the poor who come together to improve their socio-economic conditions. For that they start the various business transactions. While doing their business Self Help Groups are facing many problems like, to find the marketing potential, poor product packaging, Lack of materials, machines and equipments, getting the loan from bank, repayment of the loan, continuity, lack of awareness and Marketing their products etc., This study analyse the marketing problems faced by the self help groups of Coimbatore district.